2017
DOI: 10.15740/has/au/12.techsear(3)2017/641-647
|View full text |Cite
|
Sign up to set email alerts
|

Role of morphological characters offering resistance/ susceptibility of pigeonpea genotypes to pod borer complex

Abstract: SUMMARY :Investigation on "Studies on morphological and biochemical basis of resistance against pod borer complex in pigeonpea (Cajanus cajan L.)" was conducted, at the Research cum Instructional Farm of Indira Gandhi Krishi Vishwavidyalaya, Raipur, Chhattisgarh during Kharif -Rabi 2012-13 and 2013-14, respectively.In the genotype screening against pod borer complex viz. M. vitrata, H. armigera and M. obtusa, it was found that the germplasm ICP 6996 showed minimum larval population, minimum pod damage, minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…But in the present study, it was found that pod width did not have any significant effect on pod borer damage. Rana et al, (2017) also reported that pod wall thickness and pod trichome density are negatively correlated with pod damage in pigeon pea. Moudgal et al, (2008), Salimath et al, (2008 and Sunitha et al, (2008) also reported that trichome density on pods found to offer resistance against pod borers.…”
Section: Pod Wall Thicknessmentioning
confidence: 90%
“…But in the present study, it was found that pod width did not have any significant effect on pod borer damage. Rana et al, (2017) also reported that pod wall thickness and pod trichome density are negatively correlated with pod damage in pigeon pea. Moudgal et al, (2008), Salimath et al, (2008 and Sunitha et al, (2008) also reported that trichome density on pods found to offer resistance against pod borers.…”
Section: Pod Wall Thicknessmentioning
confidence: 90%